Electroactive microorganism-assisted remediation of groundwater contamination: Advances and challenges. (June 2023) - Feng, Huajun; Yang, Wanyue; Zhang, Yifeng; Ding, Yangcheng; Chen, Long; Kang, Ying; Huang, Huan; Chen, Ruya
Graphical abstract: Highlights: EAMs can use coexisting pollutants to promote electron transfer to assist remediation. EAMs can mitigate the low bioavailability limits of bioremediation by complex EET. EAMs can solve the problem of electron donor/acceptor imbalance by LDET and MET. Micron electrode spacing reduces energy loss due to groundwater's low conductivity. Abstract: Groundwater contamination has become increasingly prominent, therefore, the development of efficient remediation technology is crucial for improving groundwater quality. Bioremediation is cost-effective and environmentally friendly, while coexisting pollutant stress can affect microbial processes, and the heterogeneous character of groundwater medium can induce bioavailability limitations and electron donor/acceptor imbalances. Electroactive microorganisms (EAMs) are advantageous in contaminated groundwater because of their unique bidirectional electron transfer mechanism, which allows them to use solid electrodes as electron donors/acceptors. However, the relatively low-conductivity groundwater environment is unfavorable for electron transfer, which becomes a bottleneck problem that limits the remediation efficiency of EAMs. Therefore, this study reviews the recent advances and challenges of EAMs applied in the groundwater environment with complex coexisting ions, heterogeneity, and low conductivity and proposes corresponding future directions.